Multi-Modes for Detecting Experimental Measurement Error - Laroze-Prehn, D (Cambridge University Press, 2020)
Experiments should be designed to facilitate the detection of experimental measurement error. To this end, we advocate the implementation of identical experimental protocols employing diverse experimental modes. We suggest iterative nonparametric estimation techniques for assessing the magnitude of heterogeneous treatment effects across these modes. And we propose two diagnostic strategies - measurement metrics embedded in experiments, and measurement experiments - that help assess whether any observed heterogeneity reflects experimental measurement error. To illustrate our argument, first we conduct and analyze results from four identical interactive experiments: in the lab; online with subjects from the CESS lab subject pool; online with an online subject pool; and online with MTurk workers. Second, we implement a measurement experiment in India with CESS Online subjects and MTurk workers. Copyright © The Author(s) 2019. Published by Cambridge University Press on behalf of the Society for Political Methodology.